Uji Cemaran Bakteri Koliform Dan Escherichia coli Pada Berbagai Sediaan Jamu Instan Jahe Merah dan Beras Kencur Di Kabupaten Karawang - Dinda Nugrahan; Ahsanal Kasasiah; Salman Salman (Jurnal Ilmiah Wahana Pendidikan, 2022)
Jamu is a traditional Indonesian medicine. The process of making herbal medicine in general still uses simple methods that are vulnerable to contamination by various types of microorganisms that cause a decrease in the quality and safety of herbal medicine. The presence of medicinal herbs contaminated with microbes is related to the selection of raw materials, processing procedures and presentation related to the environment and workers. Testing for contamination of Coliform bacteria and Escherichia coli on liquid and powder instant herbal preparations produced in Telukjambe Timur Karawang District has been carried out by calculating the MPN number. The herbal samples were tested using 3 different preparations, namely liquid herbal samples, powder with vending water and powder with demineralized aqua. From the results of the study it was found that all negative samples contained Salmonella sp bacteria and samples of herbal rice kencur and red ginger powder prepared with sterile Aqua DM were declared negative for containing Escherichia coli bacteria. As for the kencur rice and red ginger samples, liquid and powder preparations with seller's water were positive for Escherichia coli bacteria